SOSIALISASI BAHAYA PEGGUNAAN GADGET TERHADAP KESEHATAN PADA REMAJA - Adha, Afifah Cahayani; Yunita, Alfitri Yana; Hendriani, Sisi; Nelaz, Yolanda Safitri (Awal Bros Journal of Community Development, 2025)
The rapid development of digital technology has made gadgets such as smartphones, tablets, and laptops an integral part of adolescent life. However, excessive gadget use can lead to various health problems, such as Computer Vision Syndrome (CVS), musculoskeletal disorders, and decreased sleep quality. Initial observations at SMA Negeri 10 Pekanbaru showed that 78% of students experienced CVS symptoms, 65% complained of neck and back pain, and 42% experienced sleep disturbances. Although 91% of respondents were aware of the negative impacts of gadgets, only 12% consistently limited their use. To address this, the research team implemented a participatory outreach program at SMA Negeri 10 Pekanbaru using lectures, discussions, and practical training methods such as the 20-20-20 technique, correct posture, and a digital detox workshop. The results showed a 62% increase in participant understanding based on pre- and post-tests, as well as high enthusiasm for the practical solutions provided. The program also established peer educators to ensure the continuity of education. In conclusion, interactive outreach and a participatory approach are effective in increasing awareness and changing adolescent behavior related to gadget use. It is necessary to expand similar programs to other schools to minimize the negative impact of gadgets on adolescent health.